BENTUK DAN DAMPAK PERILAKU BULLYING TERHADAP PESERTA DIDIK - Viola Amnda; Septia Wulandari; Suci Wulandari; Saskia Nabila Syah; Yopie Andi Restari; Septina Atikah; Engkizar Engkizar; Fuady Anwar; Zainul Arifin (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2020)
This research aims to explore kinds and impacts of bullying behavior toward students. This research used qualitative methods with case study approach. Data source was taken through deep interview toward 20 informants which are consists of elementary students, junior high school students, senior high school students, teachers, headmaster, security, society figures and parents. All interview data was analyzed thematically by using qualitative analysis software NVivo 10. The whole research results resulted in nine important themes related to kinds and impacts of bullying behavior toward students. Those nine themes are divided into three themes related to kinds of bullying behavior, they are i) physical appearance, ii) verbal, iii) psychology. Futhermore, six themes related to the impacts of bullying behavior, they are: i) No self-confidence, ii) intimidated, iii) inferiority, iv) insecurity, v) afraid of socializing with the environtment, vi) difficult to concentrate in learning. Bullying behavior has no place in education, but the facts show that the problems often appear repeatedly with unconditional time and place. The role of all parties not only schools, parents, and society are needed to prevent bullying behavior because based on this research bullying behavior has negative impacts on students both physically and physchology.